Intestinal angina in a patient with hypertrophic obstructive cardiomyopathy: a case report. (December 2016) - Hamaoka, Takuto; Omi, Wataru; Sekiguti, Yoshiteru; Takata, Shigeo; Kaneko, Shuichi; Inoue, Oto; Takashima, Shinichiro; Murai, Hisayoshi; Usui, Soichiro; Kato, Takeshi; Furusho, Hiroshi; Takamura, Masayuki
Abstract Background Intestinal angina is characterized by recurrent postprandial abdominal pain and anorexia. Commonly, these symptoms are caused by severe stenosis of at least two vessels among the celiac and mesenteric arteries. However, intestinal perfusion is affected not only by the degree of arterial stenosis but also by systemic perfusion. We experienced a unique case of intestinal angina caused by relatively mild stenosis of the abdominal arteries complicated with hypertrophic obstructive cardiomyopathy. Case presentation We report an 86-year old Japanese man with hypertrophic obstructive cardiomyopathy and advanced atrioventricular block who was diagnosed with intestinal angina. Computed tomography showed mild stenosis of the celiac artery and severe stenosis of the inferior mesenteric artery, and these lesions were relatively mild compared with other reports. A dual-chamber pacemaker with right ventricular apical pacing was implanted to improve the obstruction of the left ventricular outflow tract. After implantation, the patient's abdominal symptoms diminished markedly, and improvement of the left ventricular outflow tract obstruction was observed. Conclusions Although intestinal angina is generally defined by severe stenosis of at least two vessels among the celiac and mesenteric arteries, the present case suggests that hemodynamic changes can greatly affect intestinal perfusion and induce intestinal angina in the presence of mild stenosis of the celiac and mesenteric arteries.